Faktor Determinan dalam Menjalankan Inovasi Bidang Pendidikan - Arief Rahman Hakim (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to identify the determinant factors in implementing innovation in the field of education in Makassar City, using qualitative research. Based on the source, the types of data used are primary and secondary. Data obtained through interviews with the education office and principals, while secondary data is data obtained from various literature such as books, laws and other related sources. The results of the study indicate that there are 3 main determinant factors in implementing innovation in the field of education, namely a). Leadership that plays an important role in implementing innovation wisely and encouraging the enthusiasm of teachers, students and stakeholders, with the commitment of visionary leaders playing a very important role in building a culture of innovation in the midst of educational transformation. Leadership can ensure that schools face future challenges and maximize technology to improve student learning outcomes. b) A conducive school culture is important for innovation and technological development in the world of education, school culture is interpreted as the quality of school life that continues to grow and develop based on a hard work ethic and certain values ​​​​held by the school. c) Resources as the fulfillment of the need for adequate resources are important so that innovation can be implemented effectively. Educational innovation strategies involve collaboration and involvement of stakeholders, such as teachers, students, parents, school administrators, and policy makers.